Analysis of mainstream tobacco smoke particulate phase using comprehensive two‐dimensional gas chromatography time‐of‐flight mass spectrometry. Issue 6 (20th February 2013) - Brokl, Michał; Bishop, Louise; Wright, Christopher G.; Liu, Chuan; McAdam, Kevin; Focant, Jean‐François
<x xml:space="preserve">Abstract</x> Comprehensive 2D GC coupled to time‐of‐flight mass spectrometry was applied for the characterization of the particulate phase of mainstream tobacco smoke particulate. Five 3R4F research cigarettes were smoked on a rotary smoking machine under standardized conditions, total particular matter was collected on Cambridge filter pads and extracted using methanol‐based liquid extraction and dynamic headspace (DHS) approaches. Automated peak finding and mass spectral deconvolution combined with scripting and manual revision of library hits were used to evaluate the library search results. The revised peak table contained nearly 1800 individual compounds for the DHS sample and over 900 for the solvent extracted sample. These methods of extraction were shown to be complementary, leading to only 11% of repeated analytes, and their combination gave rise to a list of almost 2500 individual compounds.